Effect of Tapping System Change on the Latex Physiological Parameters in Commercial Rubber Plantations - Junaidi Junaidi; Atminingsih Atminingsih; Muhammad Rizqi Darojat; Arief Rachmawan; Andi Wijaya (International Journal of Agricultural Sciences, 2021)
Latex diagnosis was introduced to monitor plant physiological status. In this study, we observed the effect of tapping system alteration in 2019 and 2020 on the latex physiological status. Latex samples were collected from 26 blocks of 10 rubber estates in North Sumatra Province, Indonesia. The physiological parameters assessed were totally solid, sucrose, inorganic phosphorus, and thiol contents. Our observation showed that the tapping system change did not significantly affect the total solid content. In terms of sucrose content, a significant effect was detected only in tapping change from quarter spiral upward tapping d3 to d4 (7.80 mM and 2.30 mM, respectively). While, inorganic phosphorus content decreased in all tapping system alterations, suggesting a metabolic response to tapping system adjustment. According to sucrose and inorganic phosphorus contents, yield optimization could be implemented in appropriate blocks. The thiols content was not significantly affected by tapping system alteration. The RSH values ranged from 0.32 mM to 0.76 mM, suggesting a wide variation in the antioxidant level of the plant. While sucrose and thiols content showed some discrepancies to the LD theory, Pi content exhibited a dependable response, suggesting that this parameter could be a good indicator to evaluate the tapping system regime. Our result could be a beneficial input for rubber planters to maintain the physiological level to the commercial extent.